Autonomous control of grid-tied energy storage system - Zhou, Xiangyu (2016)
The shortage of sources and the pollution of the environment provides impetus for the use of renewable sources including solar energy and wind energy. But the intermittency of renewable sources may influence the power quality or even threaten the stability of the power system. This problem could be solved by implementing grid-connected energy storage system. This project aims at studying the autonomous control method for the DC-link voltage based on the bidirectional voltage source converter model. In the main parts of this project, some important knowledge in previous research is mentioned to provide basic information. After that, controllers used in the double close control loop and the state development of this simulation model are talked. The result is shown by analyzing the output image of the scope. It is recommended that the grid-connected energy storage system model should be built and an improved control method should be provided for that in further research.